BLENDED LEARNING BASED ON WASATHIYYAH: A MAQASHID SHARIAH APPROACH TO ONLINE–OFFLINE INTEGRATION IN CHILDREN’S EDUCATION - Muhammad Ghazali; Muhammad Mirzan; Afif Alfiyanto; Fitri Hidayati; Syatria Adymas Pranajaya (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2026)
The rapid digitalization of Islamic education has accelerated the adoption of blended learning, yet its predominantly technical implementation often neglects the ethical and developmental well-being of young learners. Unregulated screen exposure and algorithm-driven content frequently induce cognitive overload, moral disorientation, and diminished social interaction in primary educational settings. Addressing this gap, this study employs qualitative library research grounded in thematic tafsir (tafsir maudhu’i) to systematically extract Qur’anic principles that inform a balanced pedagogical architecture. By analyzing classical and contemporary exegetical sources alongside empirical studies published between 2020 and 2026, the research operationalizes the Islamic concepts of wasathiyyah (moderation) and maqashid al-shariah as evaluative filters for digital instruction. The findings reveal that Qur’anic discourse establishes clear operational parameters for proportional screen-time allocation, ethically curated content delivery, multidimensional assessment, and structured home-school collaboration. These parameters are synthesized into a scalable wasathiyyah-based blended learning model that dynamically aligns technological integration with the preservation of children’s intellect, psychological health, and religious identity. The proposed framework provides educators and curriculum designers with a theologically coherent, contextually adaptive blueprint for hybrid instruction. Ultimately, this research demonstrates that classical Islamic exegesis can effectively guide contemporary educational technology, ensuring that digital transformation serves holistic child development rather than compromising foundational moral and cognitive growth.